Mammals Community in Ranggawulung Urban Forest, Subang - Mhd Muhajir Hasibuan; Rizki Kurnia Tohir; Siti Rabiatul Fajri; Shinta Nur Rahmasari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Ranggawulung urban forest as one of the remaining vegetated sites in Subang city has the potential to be a strategic location for biodiversity that needs to be managed sustainably. Biodiversity studies in Rangawulung urban forest need to be conducted periodically to assess and control the impact of urban development. This study was conducted to assess biodiversity in Subang City, especially mammals community ini Ranggawulung Urban Forest as an indicator of biological management in urban areas. There were eight species of mammals found in the Ranggawulung City Forest area from five families. Diversity (H'), richness (Dmg), and evenness (E') indices of the area species were 1,09, 1,6, and 0,84. One of the species found, the Javanese slow loris (Nycticebus javanicus), is a protected animal in PermenLHK Number P.106 / MENLHK / SETJEN / KUM.1 / 12/2018. The species is also categorized as CITES Appendix I and Critical Endangered according to the IUCN red list. Ranggawulung Urban Forest is considered important as an animal habitat in Subang City and needs to be managed properly and sustainably.